Three Brajbhāṣā versions of the Bhāgavata Purāṇa - Horstmann, Monika (International journal of Hindu studies, 2018)
Central to Vaiṣṇava bhakti as it was propagated in Braj from the sixteenth century is the Bhāgavata Purāṇa. That bhakti spread to the Rājpūt courts, whose patronage spurred the production of sectarian Brajbhāṣā Bhāgavatas that added to versions not directly linked with the courts. This paper presents three vernacular Bhāgavatas, namely, the Puṣṭimārgīya Mahānand Bhāgavata (completed in 1687), the Nimbārka Bhāgavata of Brajdāsī (completed in 1755), and the Gauḍīya Bhāgavata of Vaiṣṇavadās “Rasjānī” (completed in 1774). Focusing on Bhāgavata Purāṇa 10.10, the authors’ perception of translation as a creative act and their ways of negotiating their sectarian positions are discussed.
Gesehen am 26.11.2018